2021
DOI: 10.1371/journal.pone.0250847
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of built-up areas in Ghana since 1975

Abstract: We use high resolution satellite data on the proportion of buildings in a 250x250 meter cell to study the evolution of human settlement in Ghana over a 40 year period. We find a strong increase in built-up area over time, mostly concentrated in the vicinity of roads, and also directly on the coast. We find strong evidence of agglomeration effects both in the static sense—buildup in one cell predicts buildup in a nearby cell—and in a dynamic sense—buildup in a cell predicts buildup in that cell later on and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…The intensity of growth in the central cities varied depending on their proximity to road infrastructure, which offers economic vitality and greater accessibility. Many studies have confirmed the strong effect of the road networks on urban growth patterns [ 75 ]. The spatial transformations occurred in several phases and were primarily influenced by environmental, social, political, and economic forces.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of growth in the central cities varied depending on their proximity to road infrastructure, which offers economic vitality and greater accessibility. Many studies have confirmed the strong effect of the road networks on urban growth patterns [ 75 ]. The spatial transformations occurred in several phases and were primarily influenced by environmental, social, political, and economic forces.…”
Section: Discussionmentioning
confidence: 99%